The Effect of Tunneling Incentives, Bonus Mechanisms and Debt Covenants on Transfer Pricing Decisions - Devi Ayu Putri (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
This study aims to determine the effect of Tunneling Incentive, Bonus Mechanism and Debt Convenant on Transfer Pricing Decisions. This type of research is causal associative with quantitative data types. The population in this study was 26 using purposive sampling method. Based on these criteria, there are 16 companies with a total data of 48 companies. The results show that Tunneling Incentive, Bonus Mechanism and Debt Convenant have a positive and significant effect on transfer pricing decisions, either partially or simultaneously. These results are with the predetermined hypothesis, so that all hypotheses are accepted.